(3OhGaY GNJjGQ GdeQCI degfI GdJYdje eG bHd GdLGeYj aj eOjfI UjOGs - (3TcQ, egi gGTes ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2004)
(3JgOa GdOQGSI Edi eYQaI OhGaY GNJjGQ GdeQCI degfI GdJYdje eG bHd GdLGeYj, heYQaI GdCSHGH GdcGefI hQGA GNJjGQgG gPg GdegfI heOi GdESJeQGQ ajgG(B. (3ceG JSdW GdVhA Ydi GdChVGY GdELJeGYjI, GdfaSjI, GdGbJUGOjI, GdJYdjejI hGdegfjI ddeYdeI hYdi GdeQOhO Gdegfj (B((3GdeGOj hGdeYfhj(B)(3, hcTa fhY GdYdGbI GdJj JQHWgG HQDSGFgG hRedGFgG heOi GfSLGegG eY egfJgG, hehbagG JLGggG(B. (3EYJeOJ GdOQGSI GdefgL GdJLQjHj, GdefgL GdJGQjNj, hefgL OQGSI GdMGdI(B. (3hGSJNOeJ JbfjI GdebGHdI, GdGSJeGQI, GdedGMXI, hJMdjd GdeMJhi(B. (3TedJ GdYjfI (B200 (3eYdeI deQMdI GdQhVGJ, GdEHJOGFj, GdeJhSW, hGdKGfhj ef eOGQS NGUI hQSejI aj efWbI UjOG(B. (3HjfJ GdfJGFL Cf GdeQCI GdYGedI aj eLGd GdJQHjI hGdJYdje JSGge aj GdEfaGb Ydi CSQJgG, ceG CfgG JaVd OhGe Yed bUjQ eY QGJH bdjd Ydi GdYed HOhGe Whjd Cj Cf OGaY GdGNJjGQ ddegfI gh ZjQ eGOj, agj JTYQ HGdEfLGR hGdSYGOI dCOGA GdegfI hJQHjI GdGWaGd eYkG, hJYJHQ CfgG JJjM GdaQUI ddJQbj GdhXjaj, hJHjf Cf GdeYdeI QGVjI Yf egfI GdJYdje, ef MjK GdJYGed eY GdRedGA hGdQDSGA(B. (3UQMJ GdeYdeGJ HCfgf ENJQf egfI GdJYdje chfgG JbOe YWGAGJ hJSeM ddeQCI HGdGgJeGe HYGFdJgG hHfaSgG hdCfgG JMbb dgG TNUjJgG hJTYQgG HGdCeheI HfaS GdhbJ(B. (3NdUJ GdOQGSI HCf egfI GdJYdje JJfGSH eY GdfSb Gdbjej GdSGFO GdPj jYJHQ egfI GdJYdje EeJOGOG dhXjaI GdeQCI GdQFjSjI aj GdJfTFI GdGLJeGYjI hJfSLe GdegfI eY MjGJgG GdTNUjI, hJHjf Cf JhLg GdEfGK Edi GdJNUU aj GdcdjGJ GdCOHjI jDgdgf degfI GdJYdje(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Incitation pour enseignant; Teachers incentives; (3GdGfGK OGaYjI GdeYdejfs; (3UjOGs